Experiment on the effects of storage duration of biodiesel produced from crude palm oil, waste cooking oil and Jatropha - Nanihar, Nadiarulah; Khalid, Amir; Mustaffa, Norrizal; Jaat, Norrizam; Sapit, Azwan; Razali, Azahari; Mohamed Sunar, Norshuhaila (IOP Publishing, 2017)
Biodiesel based on vegetable oil is an alternative that had various advantage in term of sustainability and environmental attractive compare to others conventional diesel. Biodiesel is product of any fat or oil that derived from any organic sources through a refinery process called transesterification process. This research investigates the effects of storage duration and variant ambient condition on the biodiesel properties and characteristics. In this study, there are three types of blending which is 5vol% blends ( 5vol% plant oil 95vol% diesel), 10vol% blending (10vol% plant oil and 90vol% diesel) and 15vol% blending (15vol% plant oil and 85vol% diesel) each called CPO5 (crude palm oil 5vol%), CPO10 (crude palm oil 10vol%),CPO15 (crude palm oil 15vol%), JO5 (jatropha oil 5vol%), JO10 (jatropha oil 10vol%),and JO15 (jatropha oil 15vol%) respectively. Biodiesel samples were stored at indoor condition and outdoor condition for a 3 months period. The fuel properties such as acid value, viscosity, density, water content and flash point are observed with the laboratory instrument. Flash point value and water content increased under both of indoor and outdoor condition and a steady data for viscosity and density. However, acid value at indoor condition nearly constant but increased dramatically for outdoor condition over the time.